Estudo da biodiversidade de fungos endofíticos, potencial citotóxico e antimicrobiano de duguetia flagellaris huber - Oliveira, Juliana Gomes De Souza (2013)
The vast expanse of the Amazon rainforest concentrates third of the total of all species on Earth. However, all this wealth suffers risk of extinction due to lack of multidisciplinary knowledge and indiscriminate use by man. Even more precarious is the absence of intraspecific information and the biotechnological potential that these may present. In the State of São Paulo were 1,009 endangered or extinct species listed in 2005 and the Database Tropical indicated 2,754 species of Brazilian plants with some degree of threat in the 90s, among which 49 are Annonaceae. As these data are not updated is to expect a much higher ratio of threatened plants. Therefore, knowledge of plant biodiversity, animal and microorganism is a challenge to the rational use and conservation of genetic diversity for future generations. The family Annonaceae, is typically of the Neotropics, has a great potential for research in the areas of botany, microbiological, genetics, biotechnology, natural products chemistry, conservation, among others. With approximately 120 genera, 2,000 species and distribution center in Regions Amazon and Guianas, the Annonaceae are potential producers of substances with biological activities, such as anticancer, antiprotozoal (leishmanicidal and antimalarial) and insecticide. These activities are assigned to two major groups of molecules: the aromatic polyketides, these unique plants and alkaloids related to antimalarial activity. Among the plant biodiversity of the Amazon Rainforest is D. flagellaris (Annonaceae) whose knowledge of their endophytes, the biotechnological potential of these and knowledge about the interaction of plant/microorganisms are nonexistent. For these reasons is that we set out to study them to research the biotechnological potential of plants and their endophytes with tests against microorganisms of medical interest and indicators of cytotoxic activity, and to investigate the interaction between endophytic fungi and host. In this study, we isolated 247 endophytic microorganisms, among these 234 are fungi resulting in a fungi colonization rate of 108.3%. The groups most frequently isolated in this study were: Phomopsis (45.4%), Fusarium (14.8%) and Colletotrichum (25.5%). The plant tissue was isolated in which the largest number of endophytic fungi was flagellum (45.4%), followed by branch (38.4%) and leaf (24.5%). However, in the branch isolated the largest number of groups (14), and leaf and flagellum, showed a lower diversity: 8 and 6 groups, respectively. According to the tested media, media BDA+AT, BDA+CT, Aveia+AT and ISP2+CT had higher rates of colonization. The plant extracts demonstrated mostly activity against at least two pathogens and a significant antimicrobial activity was presented by Branch-Hexane extract, where there was a halo of 18 mm against E. faecalis. Fungal groups mostly showed activity against at least two microorganisms. Therefore concluded that D. flagellaris has a high rate of colonization and a potential antimicrobial and cytotoxic activity, together with their endophytic fungi also demonstrated activity against important pathogens.